Total Global Dominator Coloring of Trees and Unicyclic Graphs - Chithra K. P.; Joseph Mayamma (مجلة بغداد للعلوم)
A total global dominator coloring of a graph  is a proper vertex coloring of  with respect to which every vertex  in  dominates a color class, not containing  and does not dominate another color class. The minimum number of colors required in such a coloring of  is called the total global dominator chromatic number, denoted by . In this paper, the total global dominator chromatic number of trees and unicyclic graphs are explored.